Repetitive simulation training with novel 3D‐printed sinus models for functional endoscopic sinus surgeries. Issue 4 (21st July 2022) - Suzuki, Masanobu; Miyaji, Kou; Watanabe, Ryosuke; Suzuki, Takayoshi; Matoba, Kotaro; Nakazono, Akira; Nakamaru, Yuji; Konno, Atsushi; Psaltis, Alkis James; Abe, Takashige; Homma, Akihiro; Wormald, Peter‐John
Abstract: Background: The purpose of this study was to find a utility of a newly developed 3D‐printed sinus model and to evaluate the educational benefit of simulation training with the models for functional endoscopic sinus surgery (FESS). Material and methods: Forty‐seven otolaryngologists were categorized as experts (board‐certified physicians with ≥200 experiences of FESS, n  = 9), intermediates (board‐certified physicians with <200 experiences of FESS, n  = 19), and novices (registrars, n  = 19). They performed FESS simulation training on 3D‐printed models manufactured from DICOM images of computed tomography (CT) scan of real patients. Their surgical performance was assessed with the objective structured assessment of technical skills (OSATS) score and dissection quality evaluated radiologically with a postdissection CT scan. First we evaluated the face, content, and constructive values. Second we evaluated the educational benefit of the training. Ten novices underwent training (training group) and their outcomes were compared to the remaining novices without training (control group). The training group performed cadaveric FESS surgeries before and after the repetitive training. Results: The feedback from experts revealed high face and content value of the 3D‐printed models. Experts, intermediates, and novices demonstrated statistical differences in their OSATS scores (74.7 ± 3.6, 58.3 ± 10.1, and 43.1 ± 11.1, respectively, p  < .001), and dissection quality (81.1 ± 13.1, 93.7 ± 15.1, and 126.4 ± 25.2, respectively, p  < .001). The training group improved their OSATS score (41.1 ± 8.0 to 61.1 ± 6.9, p  < .001) and dissection quality (122.1 ± 22.2 to 90.9 ± 10.3, p  = .013), while the control group not. After training, 80% of novices with no prior FESS experiences completed surgeries on cadaver sinuses. Conclusion: Repeated training using the models revealed an initial learning curve in novices, which was confirmed in cadaveric mock FESS surgeries. Level of evidence: N/A Abstract : To validate the new 3D‐printed sinus model and confirm its educational effect of them, a forty‐seven otolaryngologist; with different surgical skills performed functional endoscopic sinus surgery simulation training on 3D‐printed models manufactured from DICOM images of computed tomography (CT) scan of real patients. Their surgical performance was assessed with the objective structured assessment of technical skills score, and dissection quality was evaluated radiologically with a postdissection CT scan.